Exoesqueleto para la rehabilitación de la marcha en personas con accidente cerebro vascular. - Cobo Altamirano, José Enrique (2024)
Cerebrovascular accident is a lesion in the blood vessels at the cerebral level; it can be ischaemic or hemorrhagic. In the clinic, it is characterised by the loss of neurological functions depending on the anatomical site affected. One of the most common sequelae is the alteration of gait due to an affectation in the motor homunculus. One of the outstanding rehabilitative methods at present to treat it is the use of an exoskeleton. The present work is a bibliographic review of documentary type whose main objective is based on identifying the mechanical and physiological effects produced by the use of the exoskeleton in stroke patients to recover gait function through a compilation of bibliographic information to support its benefits. We compiled a population of 85 scientific articles by searching various databases and high impact scientific journals. Inclusion and exclusion criteria were applied, and the methodological quality of the articles was evaluated using the PEDro scale, selecting those that obtained a score equal to or higher than 6 on this scale. Finally, 25 articles corresponding to randomised clinical trials were selected and included in the study. It was shown that the use of the exoskeleton in the recovery of walking in patients with stroke causes an evident improvement in muscle strength, greater stride amplitude, joint function, and quality of life. Therefore, the benefits have a favourable impact on the functional, physical, social, and psychological aspects of the patient.